Kinetic energy recovery and reuse of traveling drive system of hybrid hydraulic electric loader - Hongli Cao (Advances in Mechanical Engineering)
During loading and unloading operations of electric loaders, the traveling system requires frequent starting and braking, a process that has high energy consumption and requires high installed power of the system drive motor. This paper proposes a hydraulic-electric hybrid loader traveling energy-saving system, describes its working principle, designs a hydraulic regenerative braking strategy and an energy-assisted starting strategy, analyzes the braking system in detail, gives a detailed analysis of the braking system, gives how to determine the parameters of the key components such as accumulators and hydraulic motors, and coordinates the powertrain of electric motors and hydraulic pumps/motors. Simulation results show that the scheme can effectively recover and reuse the kinetic energy of the loader during braking, and that it reduces the peak power of the original drive motor by about 19%, and the energy consumption of the whole machine operation by about 30%.